Formation of new narratives in the field of regional economic research - V. V. Stroev (Вестник университета)
The article studies evolution of main approaches to the study of regional economy. Over the past half a century, the research paradigm in the area of economic sciences has undergone significant changes: the theories of regional economics have changed, significantly evolving, complementing, and mutually reinforcing each other. The original objectives of regional economic research have changed, responding to modern challenges of the world community development and global crisis phenomena. As a result, as shown in the article, in recent years focus of research has shifted significantly towards analyzing strategic aspects and directions of regional development, as a result of which the relevant concepts have become less economics-centric. An important pattern of modernity has also become a new wave of scientific and technological progress, which determined regional innovation systems development and their subsequent digital transformation that also put a significant imprint on the paradigm of regional economy research.